SUFISME SEYYED HOSSEIN NASR DAN FORMALISME AGAMA DI INDONESIA - Noor, Irfan (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
The growing phenomenon of politics identity after the 1998 reform, which tends to encourage "religious communalism", should be a major concern and this should be answered by the discipline of Islamic philosophy as the challenges in building a better Indonesian nation with a better future. In this context, Seyyed Hossein Nasrâs thought is relevant to be actualized as the effort to contextualize the role of Islamic philosophy for contemporary society and as an approach to understand the reality of religion through the world-view of Sufism.